Reintegration or Recidivism? Rethinking Indonesia’s Policies Toward Former Terrorism Convicts: Reintegrasi atau Kambuh? Meninjau Kembali Kebijakan Indonesia Terhadap Mantan Narapidana Terorisme - Rohadhatul Aisy; Dheni Anugerah Prasetya; Chandan Kumar Sah (Universitas Negeri Semarang, 2026)
The recurrence of terrorism cases in Indonesia remains frequent and continues to pose a threat despite the government’s efforts to promote deradicalization programs in recent years. The implementation of these programs has yet to achieve optimal outcomes, as many former terrorism inmates rejoin their networks and engage in further acts of terrorism after release. This study aims to examine the effectiveness of deradicalization programs for former terrorism inmates in Indonesia and to formulate an ideal policy framework. Employing a qualitative approach with a socio-legal method, the findings reveal that deradicalization programs have not been effective. Contributing factors include fragmented and sectoral implementation, insufficient competence and quantity of correctional officers, prison overcrowding, the uniform treatment of terrorism inmates with general prisoners, and persistent social stigma. An ideal deradicalization policy should be implemented through systematic stages Identification, Rehabilitation, Re-education, and Resocialization by fostering synergy between government and non-government institutions using a humanistic approach. In conclusion, deradicalization programs in Indonesia remain ineffective and require comprehensive policy reformulation.